ANALISIS POLICY NETWORKS: UTILITAS DAN LIMITASI - AURADIAN MARTA; Leo Agustino (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2019)
The main problem in this paper is that there are doubts about the concept of policy network in policy studies. This doubt has been written by Dowding by debating policy networks as Methapor or Model. To that end, the article was written with the aim to discuss the development of the concept of policy network and explain the utility and limitation of the concept in explaining the policy process. Policy networks are in principle a study that seeks to explain the relationships between actors and their interests and resources in order to influence the policy process. Each actor will bring their interests and preferences and bargain between actors so that the linkage of actors form the typology of policy networks. More holistically, the utility of policy networks is directed to be able to answer the main question in network studies ie how does the network appear? How can the network remain and change? How can changes in the network occur? While the limitation of the use of the concept of policy networks is more on the empirical level that uses it in research with in-depth study because to see the complexity of actors, relationships between actors, and interests is not easy and as simple as thought.